1999
DOI: 10.1523/jneurosci.19-15-06637.1999
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylate Cyclase Activating Peptide Phase Shifts Circadian Rhythms in a Manner Similar to Light

Abstract: The endogenous circadian pacemaker in mammals is located in the suprachiasmatic nuclei (SCN) of the hypothalamus. Various cues can reset circadian rhythm phase, thereby entraining the internal rhythm to the environmental cycle, and these effects can be investigated using an in vitro method to measure phase shifts of the SCN. Although pituitary adenylate cyclase activating peptide (PACAP) is localized in retinal inputs to the SCN, it has been reported to alter clock phase only during the subjective day (Hanniba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
96
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 29 publications
(41 reference statements)
6
96
2
Order By: Relevance
“…Therefore, Glu is necessary to initiate the phase shift, but the level of PACAP participation alters the strength of the Glu signal. These observations are distinct from the recently reported effects of very low concentrations of PACAP, which appear to induce small phase changes via a non-cAMP-mediated mechanism that involves potentiation of the NMDA receptor (26), rather than crosstalk among second messengers. Together, these observations reveal a range of PACAP-Glu interactions that are significant in view of their colocalization in retinal ganglion cells that innervate the SCN (15).…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, Glu is necessary to initiate the phase shift, but the level of PACAP participation alters the strength of the Glu signal. These observations are distinct from the recently reported effects of very low concentrations of PACAP, which appear to induce small phase changes via a non-cAMP-mediated mechanism that involves potentiation of the NMDA receptor (26), rather than crosstalk among second messengers. Together, these observations reveal a range of PACAP-Glu interactions that are significant in view of their colocalization in retinal ganglion cells that innervate the SCN (15).…”
Section: Discussioncontrasting
confidence: 99%
“…Photic cues are transmitted to the SCN via the retinohypothalamic tract (RHT) (32) and entrain the SCN and its output rhythms to a 24-h day cycle. PACAP is abundant in the rat SCN, the RHT, and retinal ganglionic cells (32,33), and it has been shown to reset the circadian clock in a manner similar to light (34,35). Taken together, these reports suggest an involvement of PACAP in the regulation of central circadian rhythm in the mammalian SCN.…”
Section: Discussionmentioning
confidence: 76%
“…The putative photopigment, melanopsin, and the neurotransmitters, glutamate and pituitary adenylate cyclase-activating polypeptide (PACAP), are thought to mediate the communication of light information to the SCN because (1) melanopsin is distinctly localized in retinal ganglion cells that are endogenously responsive to light (Hattar et al, 2002); (2) glutamate and PACAP have been identified as the principal neurotransmitters of the RHT (De Vries et al, 1993;Hannibal et al, 2000;van den Pol, 1993); (3) transgenic deletion of genes encoding melanopsin, PACAP, and PACAP receptors influences the phase-shifting responses of the murine circadian clock to light (Colwell et al, 2004;Hannibal et al, 2001;Harmar et al, 2002;Ruby et al, 2002); and (4) infusion of glutamate or PACAP into the SCN phase shifts circadian rhythms in a manner comparable to light (Harrington et al, 1999;Meijer et al, 1988). Thus, neonatal EtOH exposure may chronically increase both the entraining and phaseshifting effects of light on the SCN clock by enhancing melanopsin-mediated phototransduction or by potentiating glutamate and/or PACAP function in the communication of photic signals to the SCN.…”
Section: Discussionmentioning
confidence: 99%